2014
DOI: 10.3389/fpubh.2014.00064
|View full text |Cite
|
Sign up to set email alerts
|

Does Drinking Location Matter? Profiles of Risky Single-Occasion Drinking by Location and Alcohol-Related Harm among Young Men

Abstract: In adolescents and young adults, acute consequences like injuries account for a substantial proportion of alcohol-related harm, especially in risky single-occasion (RSO) drinkers. The primary aim of the study was to characterize different drinking profiles in RSO drinkers according to drinking locations and their relationship to negative, alcohol-related consequences. The sample consisted of 2746 young men from the Cohort Study on Substance Use Risk Factors who had reported drinking six or more drinks on a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
2
5
0
2
Order By: Relevance
“…decreasing total DV by decreasing DVs in such particular locations but not in others) significantly reduces alcohol-related harm compared with holding a stable consumption in these locations. This result is consistent with previous studies indicating that drinking in discos/nightclubs or at friends' homes were more strongly related to alcohol-related problems than drinking in other locations (Bä hler et al, 2014;Casswell et al, 1993;Single & Wortley, 1993;Stockwell et al, 1992Stockwell et al, , 1993Usdan et al, 2005).…”
Section: Associations With Alcohol-related Harmsupporting
confidence: 93%
“…decreasing total DV by decreasing DVs in such particular locations but not in others) significantly reduces alcohol-related harm compared with holding a stable consumption in these locations. This result is consistent with previous studies indicating that drinking in discos/nightclubs or at friends' homes were more strongly related to alcohol-related problems than drinking in other locations (Bä hler et al, 2014;Casswell et al, 1993;Single & Wortley, 1993;Stockwell et al, 1992Stockwell et al, , 1993Usdan et al, 2005).…”
Section: Associations With Alcohol-related Harmsupporting
confidence: 93%
“…For example, alcohol licensing distinctions between “restaurants” and “bars” are becoming increasingly imprecise in California, as more and more restaurants that serve meals during the day “morph” into bars or nightclubs in the evening (Wittman, 2012; Ponicki, Gruenewald, Remer, Martin, & Treno, 2013). Since men usually have fewer childcare duties, they may go to restaurants that are less family friendly and consequently enhance both “party-like” atmospheres and aggressive behaviors (Bahler et al., 2014). Alternatively, fathers may be more likely to be disciplinarians when families go to a nice restaurant, letting the mother “off the hook.” If going out to a restaurant without children, fathers might be more prone to use physical discipline to ensure children behave for the babysitter or use physical discipline after if the report from the babysitter is that the children misbehaved.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, fathers may drink less often in public with their children, or be less likely to be “on-duty” for disciplining practices. Instead, fathers might drink more often at bars that are not welcoming to children and may potentially promote aggressive social norms (Bahler et al, 2014; Gruenewald, Remer, & LaScala, 2014). Analyses that fail to account for gender-specific risks may mask the ways that these relationships differ for mothers and fathers.…”
Section: Gender Drinking Contexts and Physical Abusementioning
confidence: 99%
“…In particular, drinking in bars/pubs, discos/ nightclubs and outdoor places (but not at home or in Increasing alcohol use in these settings was longitudinally associated with the increase in harm . Bähler et al (2014) further showed that, even when adjusting for the alcohol use of individuals, those who drank predominantly in public locations had higher risks for severe alcohol-related consequences. Complementing these findings, Dey, Gmel, Studer, Dermota, and MohlerKuo (2014) found that drinkers preferring beer were more likely to show risky drinking patterns than people with a mixed choice of beverages.…”
Section: Drinking Locationsmentioning
confidence: 98%